STANDARDIZATION OF TAMIL VERSION OF SHORT SENSORY PROFILE - DR.U.GANAPATHY SANKAR,; S.PRIYADARSHINI, (International Journal of Pharma and Bio Sciences, 2014)
The objective of this study was to standardize Tamil Version of Short Sensory Profile (SSP). Two hundred and fifty (n=250) Typically Developing Children (TDC) and hundred (n=100) Sensory Processing Disorder (SPD) children, aged 3 to 8 years were included through convenience sampling. SSP was administered individually to assess sensory processing abilities in children. The internal reliability of Tamil version of SSP was adequate and it discriminates typically developing children from SPD at .0001 level. The SSP has good internal reliability & discriminant ability. It can be used for screening the children with SPD.